2017
DOI: 10.1002/app.45738
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling alleviation and flux enhancement of electrospun PAN microfiltration membranes by embedding of para‐aminobenzoate alumoxane nanoparticles

Abstract: Membrane bioreactor (MBR) as a hybrid technology for wastewater treatment is becoming more popular for wastewater treatment. However, membrane fouling has hindered the widespread application of MBRs. Many efforts have been done for fouling mitigation. In this study, high flux and antifouling microfiltration membranes with unique surface structure, high surface porosity, and permeability were prepared by electrospinning technique. Initially, the optimum thickness of electrospun polyacrylonitrile (PAN) membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 51 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…The peaks observed at 1458 and 1129 cm −1 were referred to the stretching vibration of CO bond of amide that was formed as a result of N‐TESPO modification. In the case of AlOO‐NSPO nanoparticles, the absorption peaks at 3086 and 3297 cm −1 were referred to the stretching vibration of Al‐OH bond . The existence of the peak at 1199 cm −1 was related to the asymmetric hydrogen bond of OH … OH of the boehmite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks observed at 1458 and 1129 cm −1 were referred to the stretching vibration of CO bond of amide that was formed as a result of N‐TESPO modification. In the case of AlOO‐NSPO nanoparticles, the absorption peaks at 3086 and 3297 cm −1 were referred to the stretching vibration of Al‐OH bond . The existence of the peak at 1199 cm −1 was related to the asymmetric hydrogen bond of OH … OH of the boehmite.…”
Section: Resultsmentioning
confidence: 99%
“…PAN nanofibers were prepared via electrospinning technique, as schematically shown in Figure , which fully described in previous studies . In this study, a high voltage power supply was applied to the PAN solution in a 1 mL syringe connected to a metallic needle with length and internal diameter of 3.5 and 0.5 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[55] As per the original IP method, a microporous PES based support is immersed in an aqueous solution Reproduced with permission. [53] Copyright 2017, Wiley Periodicals, Inc. From this study, it was concluded that during cold and hot stretching, the polymer secondary crystals structures gets converted to bridged structures.…”
Section: Interfacial Polymerizationmentioning
confidence: 87%
“…[50] Among them, the hydrophilic polymers like PAN, cross-linked PVA, and CA have edge over hydrophobic polymers like PVDF because these materials resist bacterial and protein fouling. Moradi et al [53] obtained PAN-based ENM membranes for different spinning time and observed different average fiber thickness, mean pore size, and average porosity. Moradi et al [53] obtained PAN-based ENM membranes for different spinning time and observed different average fiber thickness, mean pore size, and average porosity.…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation